Quantum-inspired artificial immune system (QIAIS) for optimal load technique for loss minimization / Eda Sofia Othman - Othman, Eda Sofia (2013)
In power system restructuring, losses occur in generation and transmission may caused high cost to consumers. So that the optimum load shedding techniques are developed in order to reduce the losses thus minimize the consumer's costs. In order to solve this problem, a several techniques had been developed to optimum the load shedding. Besides that, Quantum-Inspired Artificial Immune System optimization technique is an approach for optimal load shedding in distribution system. QIAIS is a combination of Artificial Immune System and the Quantum Inspired techniques.